1997
DOI: 10.1007/s002470050217
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic factors in the variability of primary vesico-ureteral reflux with age

Abstract: The possibility of delayed maturation of the antireflux mechanism in whites is considered as a possible explanation, and the possibility of an ethnic basis for this is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 7 publications
0
22
0
4
Order By: Relevance
“…In spite of the notably conservative approach applied in group 2, this study reveals that the traditional concept of surgery as the therapy of choice to prevent kidney damage in patients with increased risk for unfavorable clinical course, high-grade VUR, and nephropathy at diagnosis [8][9][10][11] is, and still is for some health care professionals, the cause for the selection of surgery as the initial therapeutic option for these patients. It has been observed how, in spite of a trend towards conservative treatment in the pre-guideline era, patients with VUR IV-V and nephropathy at diagnosis tended to be excluded from the sequential treatment algorithm.…”
Section: Discussionmentioning
confidence: 82%
“…In spite of the notably conservative approach applied in group 2, this study reveals that the traditional concept of surgery as the therapy of choice to prevent kidney damage in patients with increased risk for unfavorable clinical course, high-grade VUR, and nephropathy at diagnosis [8][9][10][11] is, and still is for some health care professionals, the cause for the selection of surgery as the initial therapeutic option for these patients. It has been observed how, in spite of a trend towards conservative treatment in the pre-guideline era, patients with VUR IV-V and nephropathy at diagnosis tended to be excluded from the sequential treatment algorithm.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, the prevalence of VUR in the pediatric age group varies in different countries. Different studies in Western countries found that the prevalence of VUR ranges from 41% and up to 63% (5,19). Interestingly, the lowest VUR prevalence was reported in Black Americans and Jamaicans, indicting racial variations (20,21).…”
Section: Discussionmentioning
confidence: 95%
“…UU., el Reino Unido e Italia, y las tasas más bajas varían entre el 6% y el 12% en los niños afroamericanos y son del 10% en los niños jamaiquinos. 3,[11][12][13][14] En nuestro país, en un estudio con 300 pacientes, Yılmaz y col. determinaron que la tasa de RVU era del 30,9%. 15 En el estudio actual, se observó que la tasa de RVU coincidía con la bibliografía relevante y que era estadísticamente significativa cuando se analizaron los grupos por separado.…”
Section: Discussionunclassified
“…2 El reflujo vesicoureteral (RVU) es la anomalía detectada con más frecuencia en los pacientes pediátricos con infección urinaria (IU), con una incidencia del 30% al 50%, mientras que se observa nefroesclerosis en el 30% al 40% de los pacientes. 3,4 Por lo tanto, es necesario estudiar cada caso de IU pediátrica para determinar la presencia de RVU. A c t u a l m e n t e , l a g a m m a g r a f í a con ácido dimercaptosuccínico (dimercaptosuccinic acid, DMSA) es la mejor técnica de diagnóstico por imágenes disponible para detectar lesiones renales asociadas con la pielonefritis aguda.…”
Section: Introductionunclassified